Current situation of the transportation systems in the city of Quito, Ecuador: An improvement proposal (TRIM. Tordesillas, revista de investigación multidisciplinar, 2019)
The purpose of this Project is the Design of a system to evaluate the public transportation in Quito, the public transportation system in Quito and in another cities of Latin-American hasn`t had a correct planning, therefore problems in the quality of service arise, for example high waiting time, discomfort when moving, insecurity, among others.With the aim of offering a better service, the design of a mobile application is proposed, through which users can evaluate the service provided and, in turn, transporters and the Mayor's Office of the Metropolitan District of Quito will have access to this information through a web portal, so you can exercise a correct control of the service. This project was developed based on the PMBOK ́s methodology because the client is a public entity and requires more documentation and detail in the processes.
Keywords: urban transport; evaluation; quality; planning project